DEVELOPING WORDWALL-BASED FORMATIVE ASSESSMENT FOR THE PERIODIC TABLE OF ELEMENTS - Aisyah Ilmiati; Hairida Hairida; Eni Mayasari (Universitas Labuhanbatu, 2026)
Purpose – This study examines the validity of a Wordwall-based formative assessment on the periodic table of elements and evaluates the perspectives of teachers and students at a public high school in Tebas, Indonesia.Methodology – This study used a research and development (R&D) approach, focusing exclusively on the ADDIE model's development phase. Data were obtained through Likert-scale questionnaires completed by expert validators, teachers, and students. Pearson’s correlation (SPSS) was used to assess item validity, and descriptive statistics (means and percentages) were used to describe questionnaire responses.Findings – The study found that Wordwall-based formative assessments of the periodic table have high validity, confirmed by expert content validation (98.80%), media validation (98.86%), and practitioner validation (87.50%). Teacher and student feedback categories were both rated as “very interesting” (96.88% and 95.51%, respectively). Of 30 items tested, 15 were valid according to Pearson’s correlation in SPSS.Contribution – This study offers practical implications by equipping teachers with strategies for creating interactive, efficient, digitally based formative assessments that deliver rapid feedback, ultimately enhancing student engagement and learning effectiveness in high school science classes. Theoretically, this study advances understanding of how technology integration in formative assessment contributes to improved learning outcomes and enriches the quality of educational processes, providing a replicable model for similar educational contexts.